2022
DOI: 10.3389/fpsyt.2022.976035
|View full text |Cite
|
Sign up to set email alerts
|

Timing of antipsychotics and benzodiazepine initiation during a first episode of psychosis impacts clinical outcomes: Electronic health record cohort study

Abstract: The impact of timing of antipsychotics and benzodiazepine treatment during a first episode of psychosis on clinical outcomes is unknown. We present a RECORD-compliant electronic health record cohort study including patients (n = 4,483, aged 14–35) with a primary diagnosis of any non-organic ICD-10 first episode of psychosis at SLAM-NHS between 2007 and 2017. The impact of antipsychotic timing (prescription > 1 week after a first episode of psychosis) was assessed on the primary outcome (risk of any psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 68 publications
2
4
0
Order By: Relevance
“…Furthermore, we found minimal differences among diagnosis-specific subnetworks, highlighting substantial overlap in the dynamic progression of prodromal stages of UMD, BMD and PSY. This finding aligns with previous findings of transdiagnostic overlap in duration, first presentation and frequencies of prodromal features across SMD, 29 and extends them by showing transdiagnostic temporal and causal relationships between these features. These findings support the emergence of transdiagnostic early detection strategies that have previously been conceptualised in the clinical staging model [30][31][32][33][34] and the Clinical High At Risk Mental State (CHARMS 35 ) criteria, which have started to be implemented clinically.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, we found minimal differences among diagnosis-specific subnetworks, highlighting substantial overlap in the dynamic progression of prodromal stages of UMD, BMD and PSY. This finding aligns with previous findings of transdiagnostic overlap in duration, first presentation and frequencies of prodromal features across SMD, 29 and extends them by showing transdiagnostic temporal and causal relationships between these features. These findings support the emergence of transdiagnostic early detection strategies that have previously been conceptualised in the clinical staging model [30][31][32][33][34] and the Clinical High At Risk Mental State (CHARMS 35 ) criteria, which have started to be implemented clinically.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, assessments to detect individuals at clinical high risk for psychosis (CHR-P) have low specificity 47 and may be improved through additional features from our analyses. Echoing our earlier findings, 29 PSY exhibited the most distinctive pattern of relationships between prodromal features, with stronger connections compared to both UMD and BMD in symptom pairs relating to hallucinations, paranoia, tobacco use and disturbed sleep. The prominence of positive symptoms in PSY affirms the relevance of these assessments, [48][49][50] which primarily consider these symptoms.…”
Section: Discussionsupporting
confidence: 79%
“…Additionally, in our sensitivity analyses, there was a trending increased risk of subsequent A&E attendance by BDZ exposure when analysis was restricted to antipsychotic-naïve individuals, and a significant increased risk on A&E attendance when BDZ exposures from a non-benzodiazepine hypnotic were removed from analysis. Whilst this is the first study to examine the influence of BDZ exposure on clinical outcomes in CHR-P individuals, a recent EHR study in first-episode psychosis patients investigated the effects of antipsychotic and BDZ treatment (within the first week of illness onset) on clinical outcomes and found similar effects 35 . BDZ treatment prior to antipsychotic treatment (vs. after) increased the duration of medical and A&E admission in first-episode patients, whilst reducing the length of psychiatric admission 35 .…”
Section: Discussionmentioning
confidence: 97%
“…Whilst this is the first study to examine the influence of BDZ exposure on clinical outcomes in CHR-P individuals, a recent EHR study in first-episode psychosis patients investigated the effects of antipsychotic and BDZ treatment (within the first week of illness onset) on clinical outcomes and found similar effects 35 . BDZ treatment prior to antipsychotic treatment (vs. after) increased the duration of medical and A&E admission in first-episode patients, whilst reducing the length of psychiatric admission 35 . Furthermore, increased readmission to hospital has been associated with BDZ exposure in patients with chronic schizophrenia 36,37 .…”
Section: Discussionmentioning
confidence: 97%
“…Given that recent studies indicated a modulating effect of BDZ on outcomes in first-episode psychosis (Arribas, Solmi, Thompson, Oliver, & Fusar-Poli, 2022) as well as in schizophrenia (Strømme et al, 2022), the current meta-analytical study was designed to address the specific question whether baseline exposure to BDZ in CHR-P individuals impacts the longitudinal risk of transition to psychosis. (For a succinct overview of the role of anxiety and anti-anxiety treatment in CHR-P, please see 'Integrative appendix 2' in online Supplementary materials).…”
Section: Introductionmentioning
confidence: 99%